RESILIENT TRADITIONS OF ISLAMIC THOUGHT: Navigating Religion and Politics in Indonesia’s Emerging Future - Zamhasari, Zamhasari (Journal of Innovation Research and Knowledge, 2025)
This paper examines how the tradition of Islamic thought in Indonesia demonstrates resilience and the capacity for transformation in the face of contemporary socio-political changes—from identity polarization and populism, to the challenges of digital governance and environmental sustainability. Using a qualitative-interpretive approach based on literature, this study maps the philosophical foundations of resilience in Indonesian Islamic thought (ijtihad, maslahah, maqāṣid al-sharī‘ah, musyawarah/ijmā‘, and wasatiyyah), examines the dynamics of mass organizations (NU, Muhammadiyah) and the Islamist movement, and formulates the future direction of democratic, inclusive, and socially just religion-state relations. The paper’s novel contribution is the proposal of a “philosophies of resilience” framework as a lens to bridge tradition and innovation, formulate a values-based policy research agenda, and integrate the discourse of green Islam and digital ethics into the study of Indonesian religion-politics.